ICT Policy Development in lndonesia: Contestation, lmbrication or Collaboration? A case study of the Law of Electronic Transaction and lnformalion (UU ITE) (2008 - 2016) - Setyorini, Deviani (Curtin University, 2019)
This thesis seeks to understand the process of internet policy development in Indonesia. Using the Law of Electronic Transaction and Information as a case study, this thesis analyses the role that interactions between government, community groups and big business play in the policy formation process. This study found at least three important aspects to consider: involvement of multi-stakeholders; the policy making process itself; and addressing infrastructure, access and digital media literacy challenges.